Farmers' Attitudes Towards Cultivating Hybrid Rice in Bangladesh - Md Mofakhrul Islam Shah ,Will J Grant and Sue Stocklmayer A M, (Indian Journal of Extension Education, 2016)
Considered to be one of the viable options to sustain growth in rice production, hybrid rice was introduced during the1998-1999 boro season in Bangladesh. Its performance, however, simultaneously created hope and despair amongst thefarmers. Understanding farmers' attitudes towards this crop variety is therefore critical if hybrid rice is to be promotedfurther in Bangaldesh and beyond. The study was conducted to: i) assess attitudes of the farmers towards hybrid rice; ii)develop an item-wise analysis of attitudes towards hybrid rice; iii) explore the relationships between selected farmers'characteristics and their attitudes towards hybrid rice. The study was conducted in five regions of Bangladesh. Aconcurrent embedded design using a cross sectional survey was employed. The population of this study consisted of ricegrowers of the boro season. Amultistage stratified random sampling design was employed in selecting the sample of 425farmers. Data were collected through face–to–face interviews using a pre-tested and back translated questionnaire.Findings confirmed that a majority of non-adopters (67.1%) and de-adopters (68.0%) showed neutral attitudes while themajority of continuing adopters (58.9%) developed favorable attitudes towards cultivating hybrid rice. The results of thisstudy raise important considerations for extension workers, research leaders, seed traders and policy makers to refine thepolicy guidelines for the discovery, development and delivery of hybrid rice in Bangladesh.